Art as Next Terrorist Suspect. - Petrešin, Natša (Chain)
The article reports on the allegations faced by Steven Kurtz, founder of the art collective Critical Art Ensemble (CAE), of being a terrorist suspect. CAE consists of five activists coming from the fields of computer graphics, performance, photography, film, video and text art. On May 11, 2004, Steve Kurtz's wife suddenly died. The emergency medical team discovered that the cause of death was heart failure. Since Hope's death was unexpected, the local police searched the apartment. On Steve's table they found scientific material-equipment for biological research and for identifying genetically modified organisms.